The urologists’ perspective in management of lower urinary tract symptoms: the questionnaire-based evidence from nationwide survey in India - Wanve, Dipika; Khobragade, Kunal (International Journal of Research in Medical Sciences, 2026)
Background: Lower urinary tract symptoms (LUTS) encompass storage, voiding, and post-micturition disturbances, commonly associated with conditions such as benign prostatic hyperplasia (BPH), overactive bladder (OAB), and urinary tract infections (UTIs). Despite their high prevalence and significant impact on quality of life (QoL), LUTS are often under-recognized. This survey assesses urologists’ perspectives on the diagnosis and management of LUTS, focusing on real-world practices in the Indian context. Methods: A cross-sectional survey was conducted among 438 urologists in India from October 2024 to December 2024 to assess clinical practices in managing LUTS. A 20-question questionnaire captured diagnostic preferences, treatment approaches, and clinical perspectives. Responses were compiled and analyzed using Microsoft excel 365, with results presented as counts and percentages and visualized to highlight trends across participants. Results: In the survey, 80.4% of urologists reported urine culture as the most commonly performed diagnostic test. Age (62.3%) and symptom severity (34.2%) were the main factors guiding treatment decisions. For uncomplicated UTIs, 83.8% preferred Nitrofurantoin. BPH was the most frequent comorbidity with OAB (68.5%), and 53.4% identified lack of patient awareness as a major challenge. For OAB maintenance, 59.4% preferred Mirabegron monotherapy. Conclusions: The survey provides valuable insights into contemporary prescribing practices in urology. Nitrofurantoin remains the mainstay for uncomplicated UTIs, Mirabegron is increasingly adopted as first-line and maintenance therapy for OAB, and Silodosin, alone or in combination with Dutasteride or Tadalafil, is preferred in BPH, particularly in patients with comorbidities. Limited patient awareness, especially in OAB, highlights the need for improved education and greater integration of individualized, evidence-based pharmacotherapies into routine practice.